Essay on a new theory of the human capacity for representation - Reinhold, Karl Leonhard, 1758-1823 (De Gruyter, 2011)
In his own day, Karl Leonhard Reinhold was considered one of the major figures in philosophical thought of the late 18th and early 19th century. He was an important expositor of Kant's thought. He is also considered by many to have been the bridge between Kant and the later German idealists. In the English-speaking world only few translations of his work have been attempted. This imbalance is corrected in the present work - the first translation into English of Reinhold's major work from 1789. The translators provide an overview of the main currents of thought which informed Reinhold's philosophical project, as well as notes on his reading of Kant and other important thinkers of Reinhold's day. A glossary of key terms, a bibliography of scholarly work on Reinhold and suggestions for further reading are also included.